Docosahexaenoic acid supplementation in gestational diabetes mellitus and neonatal metabolic health biomarkers - Xu, Ya-Jie; Wang, Wen-Juan; Zhang, Qiu-Yi; Yang, Meng-Nan; Zhang, Lin; He, Hua; Dong, Yu; Ouyang, Fengxiu; Gao, Ying; Zhang, Jun; Zheng, Tao; Luo, Zhong-Cheng (Frontiers in Nutrition, 2023)
Background & Objective: Gestational diabetes mellitus (GDM) “programs” an elevated risk of metabolic dysfunctional disorders in the offspring, and has been associated with elevated leptin and decreased adiponectin levels in cord blood. We sought to assess whether docosahexaenoic acid (DHA) supplementation in GDM affects neonatal metabolic health biomarkers especially leptin and adiponectin. Methods: In a randomized controlled trial, singleton pregnant women with de novo diagnosis of GDM at 24-28 weeks of gestation were randomized to dietary supplementation of 500 mg DHA per day (intervention, n=30) until delivery or standard care (control, n=38). The primary outcomes were cord blood leptin and total adiponectin concentrations. Secondary outcomes included high-molecular-weight (HMW) adiponectin and insulin-like growth factor-1 (IGF-1) concentrations in cord blood, maternal glycemic control post-intervention and birth weight (z score). In parallel, 38 euglycemic pregnant women were recruited for comparisons of cord blood biomarkers. Results: There were no significant differences in cord serum leptin, total and HMW adiponectin and IGF-1 concentrations between DHA supplementation and control groups (all P >0.05). Maternal fasting and 2-h postprandial blood glucose levels at 12 weeks post-intervention were similar between the two groups. The newborns in the DHA group had higher birth weight z scores (P=0.02). Cord blood total and HMW adiponectin concentrations were significantly lower in GDM vs. euglycemic pregnancies. Conclusions: DHA supplementation at 500 mg/day in GDM women did not affect neonatal metabolic biomarkers including leptin, adiponectin and IGF-1. The results are reassuring in light of the absence of influence on neonatal adipokines (leptin and adiponectin), and potential benefits to fetal growth and development. Trial registration number (https://register.clinicaltrials.gov/): NCT03569501